Pleiotropic Antithrombotic Effects of Cardiovascular Drugs - Ehr, Alexander von; Bode, Christoph; Hilgendorf, Ingo (Cardiology and Cardiovascular Medicine, 2020)
Cardiovascular drugs are cornerstones of treatment of various cardiovascular diseases in clinical and outpatient practice. Commonly used cardiovascular drugs such as statins and antihypertensive medication rank among the top 10 prescribed drugs in the United States. Although primarily administered to lower blood lipid, blood sugar or blood pressure levels, many of the drugs, administered to cardiovascular patients, have been reported to exert ancillary effects that contribute to their favorable risk-benefit profiles. The aim of this non-systematic review is to give an overview about the pleiotropic antithrombotic effects of cardiovascular drugs, and to discuss the potential underlying biochemical mechanisms and their clinical relevance.